Peroni u funkciji željezničkog prigradskog prometa - Antun Stipetić (Promet - Traffic&Transportation, 1970)
This paper deals with the review of the existing conditions of platforms in the area of integration of the railways into the system of urban and suburban passenger transport in the City of Zagreb, and sets forth the recommendations of engineering (technical) resolutions for the construction of new platforms.